2016
DOI: 10.1007/s00590-016-1869-5
|View full text |Cite
|
Sign up to set email alerts
|

Combining a novel leucocyte–platelet-concentrated membrane and an injectable collagen scaffold in a single-step AMIC procedure to treat chondral lesions of the knee: a preliminary retrospective study

Abstract: AMIC combined with the CLP-MB membrane, and Cartifill seems to be a promising approach to treat knee chondral defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…The high density of RBCs, which are usually absent in most of the PRHs, is not relevant in the perspective of clinical application. LFPms are currently used in some preliminary clinical trials at the Orthopedic Department of Belluno Hospital (D'Antimo, Biggi, Borean, Di Fabio, & Pirola, ). Thus, they have already been tested for both autologous and allogeneic implants (preserving ABO/Rh compatibility) with no differences in the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The high density of RBCs, which are usually absent in most of the PRHs, is not relevant in the perspective of clinical application. LFPms are currently used in some preliminary clinical trials at the Orthopedic Department of Belluno Hospital (D'Antimo, Biggi, Borean, Di Fabio, & Pirola, ). Thus, they have already been tested for both autologous and allogeneic implants (preserving ABO/Rh compatibility) with no differences in the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 and 5 year-follow ups, clinical scores [International Knee Documentation Committee (IKDC) functional scores, Visual Analogue Scale (VAS) pain], as well as MRI and Mocart scores revealed that the addition of platelet concentrates significantly improved microfractures outcome, with PRF ensuring better and earlier results than PRP [84]. Similarly, the work by D’Antimo and Collaborators [85] retrospectively investigated the regenerative effect of microfracture technique and the concomitant application of an autologous leucocyte- and platelet-rich fibrin membrane (CLP-MB). This hemocomponent is produced through blood collection by multiple apheresis cycles to obtain a leucocyte–platelet concentrate which is added to a plasma cryoprecipitate [9,10].…”
Section: Prf In Cartilage Tissue Engineeringmentioning
confidence: 95%
“…Zwei Level-IV-Studien [31,37] mit insgesamt 38 Patienten und einem Follow-up von maximal 12 Monaten liegen für ChondroFiller gel (Amedrix GmbH, Esslingen, Deutschland) vor. In einer Studie, in der mehr als 50 % der Patienten nicht ihr Einverständnis für die Behandlung mit dem Biomaterial gaben und daher der Kontrollgruppe zugeführt wurden, war das Ergebnis im IKDC Score (International Knee Documentation Committee) in der Chondro-Filler gel -Gruppe nach 12 Monaten signifikant besser als präoperativ [37].…”
Section: Technische Aspekte Und Empfehlungen Für Débridement Und Markunclassified